Large investment of stored nitrogen and phosphorus in female cones is consistent with infrequent reproduction events of Pinus koraiensis, a high value woody oil crop in Northeast Asia - Wu, Haibo; Zhang, Jianying; Rodríguez-Calcerrada, Jesús; Salomón, Roberto L.; Yin, Dongsheng; Zhang, Peng; Shen, Hailong (Frontiers in Plant Science, 2023)
Pinus koraiensis is famous for its high-quality timber production all the way and is much more famous for its high value health-care nut oil production potential since 1990’s, but the less understanding of its reproduction biology seriously hindered its nut productivity increase. Exploring the effects of reproduction on nutrient uptake, allocation and storage help to understand and modify reproduction patterns in masting species and high nut yield cultivar selection and breeding. Here, we compared seasonality in growth and in nitrogen ([N]) and phosphorus ([P]) concentrations in needles, branches and cones of reproductive (cone-bearing) and vegetative branches (having no cones) of P. koraiensis during a masting year. The growth of one- and two-year-old reproductive branches was significantly higher than that of vegetative branches. Needle, phloem and xylem [N] and [P] were lower in reproductive branches than in vegetative branches, although the extent and significance of the differences between branch types varied across dates. [N] and [P] in most tissues were high in spring, decreased during summer, and then recovered by the end of the growing season. Overall, [N] and [P] were highest in needles, lowest in the xylem and intermediate in the phloem. More than half of the N (73.5%) and P (51.6%) content in reproductive branches were allocated to cones. There was a positive correlation between cone number and N and P content in needles (R2 = 0.64, R2 = 0.73) and twigs (R2 = 0.65, R2 = 0.62) of two-year-old reproductive branches. High nutrient sink strength of cones and vegetative tissues of reproductive branches suggested that customized fertilization practices can help improve crop yield in Pinus koraiensis.